Inkjet printed patterned bank structure with encapsulated perovskite colour filters for modern display. Issue 22 (24th May 2022) - Kang, Chengbin; Zhou, Zhicong; Halpert, Jonathan E.; Srivastava, Abhishek K.
Abstract : This work explores a new ink composition with oleylamine (OLA) and hexylphosphonic acid (HPA) ligands in combination with a liquid crystal monomer (LCM) composing a superior solution for an inkjet-printed colour conversion layer. Abstract : Inorganic multicolour perovskite nanocrystals (NCs) of CsPbX3 (X = Cl, Br, I) with high photoluminescence (PL) quantum yield (QY) and saturated colours are considered promising candidates for a high-performance colour conversion layer. However, integration of these materials into industrial applications still faces a significant challenge due to their tendency for aggregation and quenching of the emission during deposition and processing. In this work, we explore a new ink composition with oleylamine (OLA) and hexylphosphonic acid (HPA) ligands in combination with a liquid crystal monomer (LCM) composing a superior solution for an inkjet-printed colour conversion layer. This work provides a simple technique for preparing high-quality perovskite pixels for high-performance displays.